Ploidy levels affect phenotype and cytogenetic traits in Zea mays ssp. mays (2n=20 or 40) and Zea mays ssp. parviglumis hybrids - Molina, María del Carmen (2001)
The aim of this study was to analyse phenotype and cytogenetic behaviour of Zea mays ssp. mays and Zea mays ssp. parviglumis (Zpa) hybrids with different ploidy levels. Maize 2n=20 (Zm20) and Zpa hybrid plants (MPa20) were obtained naturally, they showed regular meiosis and fertile progeny (+80%). Otherwise, maize 2n=40 (Zm40) and Zpa hybrids (MPa30) were obtained by embryo rescue, they showed irregular meiosis and sterile progeny (0-8%). Meiotic configurations more frequently observed in the species and the hybrids were: Zm20 (10II); Zm40 (3.24II+8.34IV); Zpa (0.46I+9.76II); MPa20 (0.40I+9.54II+0.05III+0.65IV); MPa30 (5.97I+5.93II+4.05III). After colchicine treatment the number of IV increased in Zm20, Zpa and MPa20 and 10III were observed MPa30, because of homoeologous chromosomes pairing. In conclusion, Zm20 (AmAm BmBm) and Zpa (ApaApa BpaBpa) are allotetraploids with 2 homoeologous genomes. Whilst in the hybrids, the homoeologous genomes A pair in all cases, genomes B only do if their homologous competing during pairing, does not exist except in colchicine-treated plants which also show homoeologous genomes B pairing.